Evaluation of Preoperative Weight Loss for Elective Hernia Repair in the Veteran Population. Issue 10 (October 2017) - Sun, Beatrice J.; Valdez, David; Duong, Dao; Gupta, Ryan; Smith, Brian R.
The safety and efficacy of preoperative weight loss before elective nonbariatric surgery is controversial. We evaluated the effect of planned surgical delay for a preoperative weight loss trial in hernia repairs. Four hundred and fourteen patients undergoing elective hernia repair between July 2008 and May 2012 at a Level 1B VA Medical Center were identified. Included patients were divided into two groups: those who underwent immediate hernia repair (nontrial) and those who underwent weight loss trial before hernia repair (TRIAL). Twenty-two patients were categorized in the TRIAL group, and 392 in nontrial. Time from surgical evaluation to operation was longer in the TRIAL vs nontrial group (226 days vs 113 days, P = 0.001). Outcome measures were similar between groups. Net change in body mass index (BMI) was -2.2 per cent in TRIAL vs -0.86 per cent in nontrial patients (P = 0.440). Of the TRIAL patients, ten obtained a poor result (<3% decreased BMI), nine a moderate result (3–10% decreased BMI), and three a good result (>10% decreased BMI). Weight loss trials in elective hernia patients appear to be safe, although they result in significant delay to surgery and confer no difference in postoperative outcomes. Thus, efficacy of preoperative weight loss trials may be limited.